Numerical prediction on microstructure evolution for multi-stage hot forging of micro-alloyed piston. Issue 5 (1st July 2014) - Chen, Jun; Wang, Jin
Abstract : Purpose: – The purpose of this paper is to build a flow stress model and microstructure evolution models which can be used to fulfill the multi-physics prediction of hot forging process, in this way the process design can be virtually verified and optimized. This is especially crucial for micro-alloyed steel forging which microstructure determines the component properties, since the downstream quenching is usually not needed. Design/methodology/approach: – First, hot compression tests have been completed; second, experimental data are used to build the flow stress model and models for microstructure evolution; third, programming has been finished to integrate the proposed models into the commercial finite element method (FEM) code; fourth, case study is conducted to simulate multi-stage hot forging process of micro-alloyed steel F38MnV piston; and fifth, simulation results are validated by experiment. Findings: – First, simulation results in grain size and phase volume fraction are in well agreement with experimental ones; second, the austenite grain is dramatically refined by the dynamic recrystallization in pre-forging process and static recrystallization in the two intervals has no obvious change during the following final forging and cooling above the Ae3 temperature; third, during the cooling process below the Ae3 temperature, ferrite and pearlite transformation begin from the thin skirt to the thick skirt and piston bottom because of different cooling speeds at different areas. Originality/value: – First, flow stress model, dynamic recrystallization model, static recrystallization model, austenite grain growth model and phase transformation models are established for a micro-alloyed steel; second, the multi-physics FEM simulation of multi-stage hot forging of industrial piston has been conducted and verified by experiment, which show good agreement.